YSD UNIB 12 SOLAR DRYER PERFORMANCE FOR ROBUSTA CAFFEE DRYING - Simon Julian Sastro; Yuwana Yuwana; Evanila Silvia (BPFP Faperta UNIB, 2014)
This article presents the results of research that aims to determine the performance of the dryer YSD UNIB 12 in dry Robusta coffee. Observation parameters are divided into two test groups, namely: Test performance of the dryer without a test load and dryers with load performance. Parameter observations on no-load test include temperature and relative humidity in the dryer and outside the dryer (control) while the parameters of observation to the test with a load includes temperature and humidity inside and outside the dryer, coffee moisture content decreased with the thickness of the drying 5 cm, 7 cm and 9 cm and capacity dryers. From the no-load test observations, the average temperature conditions outside air ranged between 26°C - 33°C and relative humidity of 63% - 92%, smoking can increase the drying chamber temperature between 30°C - 45°C and relative humidity 43% - 82%. Test observations with the load on the outside air conditions 29°C - 32°C and a relative humidity of 59% - 79%, the temperature inside the kiln reaches between 36°C - 40°C and relative humidity ranged between 44% - 58% while decreasing moisture content of coffee following equation MC = 59.61 e-0, 03t for drying 9 cm thickness, MC = 61,16e-0, 03t for drying 7 cm thickness and MC = 62.39e-0, 03t for drying thickness of 5 cm. Of these equations are known to use the dryer drying speed is slower than the traditional drying but use a dryer can save an area of 1,09-fold.